2022
DOI: 10.1128/mbio.03442-21
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study after Sputnik V Vaccination Shows Durable SARS-CoV-2 Neutralizing Antibodies and Reduced Viral Variant Escape to Neutralization over Time

Abstract: Vaccines have been produced in record time for SARS-CoV-2, offering the possibility of halting the global pandemic. However, inequalities in vaccine accessibility in different regions of the world create a need to increase international cooperation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 15 publications
6
17
0
Order By: Relevance
“…In line with previous results reported for Sputnik V ( 14 ) and others ( 42 ), we observed a progressive waning in specific antibody titers up to 6 months after immunisation. Particularly, Oviedo-Rouco and collaborators ( 43 ) showed that antibody levels in older adults with a homologous scheme for BBIBP-CorV decrease significantly from 21 up to 220 days post vaccination.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with previous results reported for Sputnik V ( 14 ) and others ( 42 ), we observed a progressive waning in specific antibody titers up to 6 months after immunisation. Particularly, Oviedo-Rouco and collaborators ( 43 ) showed that antibody levels in older adults with a homologous scheme for BBIBP-CorV decrease significantly from 21 up to 220 days post vaccination.…”
Section: Discussionsupporting
confidence: 93%
“…The study evaluated 851 nursing home residents that received one of the following homologous vaccine platforms: Sputnik V (n=522), BBIBP-CorV (n=165) or AZD1222 (n=164); of the initial cohort, 693 participants reached the end of the follow-up (18.6% loss). The immune response was evaluated by measuring IgG anti-Spike titers using a well-established ELISA test ( 12 ) and neutralising capacity against a VSV-Spike pseudotyped virus ( 14 ), as well as against live ancestral B.1 and Omicron SARS-CoV-2 strains. General information about participants enrolled in this cohort, including gender, age, previous exposure to SARS-CoV-2 and comorbidities by vaccine is listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elderly volunteers with detectable anti-RBD antibodies at baseline, developed higher antibody titers within 14 days of vaccination, similar to what has been shown before in younger individuals [19,[24][25][26][27]. These results emphasize the importance of administering, in elderly individuals, at least two doses of Gam-COVID-Vac in order to achieve a robust immune response, especially in individuals without a previous SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 85%
“…Considering previous studies indicating that antibody responses undergo a maturation process, 3 , 4 we analysed the serum neutralising activity over time against the omicron variant. To this aim, we assessed the neutralising activity elicited by the Sputnik V vaccine 5 using the original B.1 isolate and a local isolate of BA.1 omicron. For this analysis, we used 60 samples (20 samples per timepoint) with the highest neutralising GMT for the original B.1 virus.…”
mentioning
confidence: 99%